RANCANG BANGUN ALAT MONITORING PERKEMBANGAN PASIEN PASCA STROKE BERBASIS IoT (INTERNET of THINGS) - Selviana Selviana; Mery Subito; Rizana Fauzi; Alamsyah Alamsyah (Foristek, 2021)
The design of this IoT (Internet of Things)-based post-stroke patient monitoring tool was built to monitor patient progress remotely. Flex sensor hardware was used to retrieve data from every movement of the patient's finger muscle strength, then processed by the NodeMCU ESP32 after that the data will be sent to the web server via the IoT platform using a local wireless network. The results of research on the development of post-stroke patients can be displayed to a web server in the form of a table plot of data values for the index finger, middle finger, and ring finger. The post-stroke patient monitoring system can be accessed on PC and Android devices. The results of the sample test from the device obtained the highest value of 3.26 MMT and the lowest value of 0.2 MMT so that the patient's finger muscle strength was declared unstable and frequent changes in muscle strength.